Zu Brugschs unveröffentlichter Bearbeitung „Ueber die libyschen Völker im 14. und 13. Jahrhundert vor Chr. Geb.“: Ein wissenschaftsgeschichtlicher Beitrag - Konrad, Kirsten (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
In 1877 Heinrich Brugsch, the founder of the ZÄS, mentioned a publication in print concerning foreign peoples in his „Geschichte Ägyptens unter den Pharaonen“. However, the work entitled „Ueber die libyschen Völker im 14. und 13. Jahrhundert vor Chr. Geb.“ should never appear. Six sheets from the estate of Ernst Weidenbach’s great-granddaughter can now be identified as part of this once announced work.